2011
DOI: 10.1007/s11745-010-3524-y
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Monounsaturated Fatty Acids Are Protective Against Metabolic Syndrome and Cardiovascular Disease Risk Factors

Abstract: Over 50 years of research has sought to define the role dietary fat plays in cardiovascular disease (CVD) risk. Although optimal dietary fat quantity has been keenly pursued over past decades, attention has recently centered on the value of dietary fat quality. The purpose of the present review is to provide a critical assessment of the current body of evidence surrounding efficacy of dietary monounsaturated fatty acids (MUFA) for reduction of traditional risk factors defining metabolic syndrome (MetS) and CVD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
313
0
13

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 445 publications
(333 citation statements)
references
References 139 publications
7
313
0
13
Order By: Relevance
“…Different views also exist about the effect of dietary MUFA, and the focus of the debate is the size of the positive effect on controlling chronic disease. According to most of recent reviews, a positive role of dietary MUFA should be existing for human beings, but further researches are needed to elucidate the mechanisms of generating the positive effect (Gillingham et al, 2011;Livingstone et al, 2012;Schwingshackl et al, 2011a,b). In the present study, MUFA were found to display a declining trend in muscle with increased dietary lipid concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Different views also exist about the effect of dietary MUFA, and the focus of the debate is the size of the positive effect on controlling chronic disease. According to most of recent reviews, a positive role of dietary MUFA should be existing for human beings, but further researches are needed to elucidate the mechanisms of generating the positive effect (Gillingham et al, 2011;Livingstone et al, 2012;Schwingshackl et al, 2011a,b). In the present study, MUFA were found to display a declining trend in muscle with increased dietary lipid concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…We also evaluated positively the absence of SFA and trans-rich fats, due to their known relationship with CVD and other chronic non-transmittable illnesses (40)(41)(42) . MUFA:SFA, widely used as an indicator of the quality of fats in the diet, was also taken into account in our index (26,30,43) .…”
Section: Discussionmentioning
confidence: 99%
“…Nuts are rich in mono-(MUFA) and polyunsaturated fatty acids (PUFA), vegetable proteins, dietary fiber, phytosterols, polyphenols, vitamins and minerals (Phillips, Ruggio, & Ashraf-Khorassani, 2005;Segura, Javierre, Lizarraga, & Ros, 2006). Most of those compounds have antioxidant properties and are proven to provide a beneficial effect on plasma lipid profile, low-density lipoprotein (LDL) oxidation and inflammatory processes, among others (Carlson, Eisenmann, Norman, Ortiz, & Young, 2011;Egert, Kratz, Kannenberg, Fobker, & Wahrburg, 2011;Gillingham, Harris-Janz, & Jones, 2011;Jones et al, 2011;Liu, 2012;Myers & Allen, 2012;H. A.…”
Section: Nuts and Nut Milksmentioning
confidence: 99%